Comprehending 3D Diagrams: Sketching to Support Spatial Reasoning. (25th November 2016) - Gagnier, Kristin M.; Atit, Kinnari; Ormand, Carol J.; Shipley, Thomas F.
Abstract: Science, technology, engineering, and mathematics (STEM) disciplines commonly illustrate 3D relationships in diagrams, yet these are often challenging for students. Failing to understand diagrams can hinder success in STEM because scientific practice requires understanding and creating diagrammatic representations. We explore a new approach to improving student understanding of diagrams that convey 3D relations that is based on students generating their own predictive diagrams. Participants' comprehension of 3D spatial diagrams was measured in a pre‐ and post‐design where students selected the correct 2D slice through 3D geologic block diagrams. Generating sketches that predicated the internal structure of a model led to greater improvement in diagram understanding than visualizing the interior of the model without sketching, or sketching the model without attempting to predict unseen spatial relations. In addition, we found a positive correlation between sketched diagram accuracy and improvement on the diagram comprehension measure. Results suggest that generating a predictive diagram facilitates students' abilities to make inferences about spatial relationships in diagrams. Implications for use of sketching in supporting STEM learning are discussed. Abstract : Sketching has been hypothesized to have many potential benefits for students in STEM disciplines. In Gagnier et al.'s paper, "Comprehending 3D Diagrams: Sketching to Support Spatial Reasoning, ‐ the authors explore whether it can help students understand diagrams that involve 3D relations. Their results suggest that generating a sketch that predicts these depicted relations is a particularly helpful, certain more than copying without making predictions or making predictions without sketching. Given the prevalence of these diagrams across STEM, this has wide reaching positive implications.